Mitochondria-Targeted Antioxidant Therapeutics for Traumatic Brain Injury - Hiren R. Modi; Sudeep Musyaju; Meaghan Ratcliffe; Deborah A. Shear; Anke H. Scultetus; Jignesh D. Pandya (Antioxidants, 2024)
Traumatic brain injury (TBI) is a major global health problem that affects both civilian and military populations worldwide. Post-injury acute, sub-acute, and chronic progression of secondary injury processes may contribute further to other neurodegenerative diseases. However, there are no approved therapeutic options available that can attenuate TBI-related progressive pathophysiology. Recent advances in preclinical research have identified that mitochondria-centric redox imbalance, bioenergetics failure and calcium dysregulation play a crucial role in secondary injury progression after TBI. Mitochondrial antioxidants play an important role in regulating redox homeostasis. Based on the proven efficacy of preclinical and clinical compounds and targeting numerous pathways to trigger innate antioxidant defense, we may be able to alleviate TBI pathology progression by primarily focusing on preserving post-injury mitochondrial and cerebral function. In this review, we will discuss novel mitochondria-targeted antioxidant compounds, which offer a high capability of successful clinical translation for TBI management in the near future.